The Role of Visual Experience in Changing the Size of Objects in Imagery Processing. (January 2015) - Szubielska, Magdalena; Marek, Bogusław
Introduction: This paper investigates the question of whether or not subjects who are congenitally blind experience greater difficulties mentally in resizing images of objects than those who have low vision or are adventitiously blind. Methods: Two experiments were conducted: one in which subjects were asked to mentally enlarge objects they previously explored manually, and one in which subjects were tested for the ability to demonstrate the change in the size of an object imagined to be moving away. Three groups of high school students with visual impairments took part in the experiment: congenitally blind, "late blind, " and those with low vision. Results: When showing the linear size of an object enlarged in their imagination, congenitally blind participants overestimated its size more frequently than those who were late blind. The degree of mental reduction of the size of an object imagined to be moving away was comparable for all groups. Discussion: The results suggest that the difficulties experienced by congenitally blind participants with the mental resizing of objects may be related to problems with performing mental scaling transformations. In the low vision group, the etiology of the subjects' visual impairment was not taken into consideration. The group turned out to be heterogeneous with respect to imagery processes. Implications for practitioners: When using models for explaining new concepts, it is important to ensure that congenitally blind learners understand the change of scale.